Condição de saúde bucal e qualidade de vida de usuários de substâncias psicoativas em atendimento nos centros de atenção psicossocial álcool e drogas da Região Metropolitana de Vitória, ES - Bissoli, Bruna Costa (2016)
Drug use is a reality and its effects are observed in the social, cultural and economic, as well as in health field. This study aimed to assess the prevalence of dental caries, as well as its impact on quality of life of drug users of Centros de Atenção Psicossocial Álcool e outras drogas (CAPS AD) in the municipalities of Vitória, Serra and Vila Velha, ES, Brazil. Developed a cross-sectional observational study, from June 2015 to February 2016, with a final sample of 280 individuals. We used the interview technique with registration in form for sociodemographic and health characteristics, the use of psychoactive substances (SPA) and the subjective indicator Oral Health Impact Profile (OHIP). Clinical examination was carried out of the dental elements to obtain the decayed, missing, and filled teeth (DMFT) index. Statistical analysis using the chi-square test was performed. We calculated the odds ratio (OR) with 95% confidence interval. A significance level of 5% in the study was adopted. The data were analyzed using the Statistical Package for Social Sciences (SPSS) version 20.0. The prevalence of caries was 96.8% (n = 271), the mean DMFT of 11.45 (SD = 7.5) and the median was 10. Age, race/color and marital status were statistically associated with DMFT> 10, as well as use and need of use of prosthesis and time of use of psychoactive substances. The impact on quality of life was significant in the dimensions psychological discomfort, psychological disability and physical pain, interfering with essential conditions of individuals. Drug users have poor oral health, with high prevalence of dental caries, which reflects in a high impact on the quality of life of these individuals. CAPS AD represent the alternative of full attention to drug users and the relationship of this space with the primary care dental service becomes extremely necessary.